(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the role of pragmatics in cross-cultural communication, highlighting the challenges that arise due to linguistic and cultural differences. It examines key pragmatic concepts such as speech acts, implicature, and politeness strategies, discussing their impact on effective intercultural interaction. The study also suggests practical strategies to overcome pragmatic misunderstandings and enhance communication across cultures.